Palatoplasty in children: nursing diagnoses and interventions related to the immediate postoperative period - Ana Flávia Martinez; Nayara Tomazi Batista; Gesiane Cristina Bom; Cláudia Regina Matiole; Carmen Silvia Zamboni; Armando dos Santos Trettene (SciELO, 2022)
Abstract Objective: To identify the main nursing diagnoses and interventions in children in the immediate postoperative period of palatoplasty. Method: Documentary and retrospective study, developed in a Brazilian public and tertiary hospital, between August and September 2020. Children who underwent only palatoplasty, between January and December 2019, aged between 10 and 24 months, were included. Those with medical syndromes and/or comorbidities were excluded. The Theoretical Framework of Basic Human Needs and the NANDA International and Nursing Interventions Classification Taxonomies were used. Data underwent descriptive statistical analysis. Results: The sample consisted of 126 children. Psychobiological needs such as oxygenation, hydration, nutrition, elimination, cutaneous-mucosal and physical integrity, pain and environmental perception predominated. Based on them, nine nursing diagnoses, with four focusing on the problem and five on risk, as well as 17 interventions, were identified. Conclusion: The use of standardized languages to identify affected human needs and, based on them, diagnoses and interventions, favored clinical reasoning for the construction and organization of clinical nursing practice.